Small-Size Betatron for the Energy 2.5 MeV for Field Inspection - Volkov V. G. Vladimir Grigorievich; Zrelov Yu. D.; Kasyanov (Kas'yanov) V. A. Valery Alekseevich; Filimonov A. A. Anatoly Alekseevich; Chakhlov V. L. Vladimir Lukianovich; Shtein M. M. Mikhail Mikhailovich (Radiology and radiography methods, 2010)
The title screen.